Infertility and lifestyle factors: how habits shape reproductive health - Priyanka Choudhary; Pooja Dogra; Kajal Sharma (Middle East Fertility Society Journal)
Abstract Background Infertility is a public health concern. It is a condition that develops when a couple is unable to conceive a child after a year of consistent, unprotected sexual activity. Infertility can be classified as either primary or secondary. Globally, approximately 17.5% of adults, or approximately one in six, experience infertility, according to the World Health Organization. Various factors, including age-related factors, diet and nutrition, sedentary lifestyle, stress factors, weight, caffeine consumption, apparel choices, exposure to heated water, and digital technology, can be associated with reproductive well-being. Main body Age, diet, exercise, obesity, smoking, excessive alcohol usage, and recreational drug use affect infertility. Age greatly affects infertility. Ageing affects all genders’ fertility. Egg number and quality decline with age, causing fertility loss after 35. Some studies show that continuous exposure to nonionizing radiation, especially from mobile devices and laptops, may decrease sperm motility and increase DNA breakage in males. Concerns concerning male infertility arise. Few data suggest electromagnetic waves may affect women’s reproductive health. However, hot baths, saunas, and exercise trigger the endocrine system as well as clothing affecting reproductive health in women differently than in males. Tight clothing, especially vaginal apparel, traps moisture and heat, raising yeast and bacterial vaginosis risk. Children, pregnant people, and mental health patients may be particularly susceptible to coffee’s side effects. A healthy weight improves sperm quality and reproductive potential; hence, weight control is an important infertility therapy. Unsurprisingly, stress may cause and worsen infertility. Stress from infertility may also affect people and couples. Moderate to severe exercise was a prevalent protective factor against infertility. A diet rich in healthy fats, fish, poultry, whole grains, fruits, and vegetables boosts male and female fertility. Conclusion Individuals can improve their health by changing their lifestyle. Awareness, lifestyle changes, and medical interventions for people and couples can improve fertility and reproductive health.